(untitled) (TAJ: Journal of Teachers Association, 2009)
Scientists and clinicians must become familiar with the factors that affect the emotional, physical, and spiritual health of their patients that are outside the ken of the traditionally dominant value systems. Although many researchers have addressed the cultural and ethnical factors, very few have considered the impact of religion. Islam, as the largest and fastestgrowing religion in the world, has adherents throughout the world, presents a complete moral, ethical, and medical framework, while it sometimes concurs conflicts with the conventional and secular ethical framework. This paper introduces to the Islamic principles of ethics in organ transplantation involving human subject to address issues of religion and religious ethics. Historical reflections are discussed as to why Muslim thinkers were late to consider contemporary medical issues such as organ donation. Islam respects life and values need of the living over the dead, thus allowing organ donation to be considered in certain circumstances. The sources of Islamic law are discussed in brief to see how the parameters of organ transplantation are derived. The Islamic perception, both Shiite and Sunni, is examined in relation to organ donation and its various sources. The advantages and disadvantages of brain dead and cadaveric donation are reviewed with technical and ethical considerations. The Islamic concept of brain death, informed and proxy consent are also discussed. The concept of rewarded donation as a way to alleviate the shortage of organs available for transplantation is assessed. doi: 10.3329/taj.v21i1.3230 TAJ 2008; 21(1): 97-103